Answer:
x = -2
y = 3
Explanation:
You are given a system of two linear equations:
-2x + 3y = 13
3x + 4y = 6
One of the good ways to solve this system is trying to eliminate one variable (x or y), calculate the remaining variable and substitute the calculated variable back into system to solve for eliminated variable.
Here, we will manipulate the original system, so that we can easily eliminate x.
Let's multiply both sides of the first equation by 3 and the second equation by 2 (this manipulating step does not change the original system of equations).
3*(-2)x + 3*3y = 3*13
2*3(x) + 2*4y = 2*6
<=>
-6x + 9y = 39
6x + 8y = 12
Now, we add up two equations, left side + left side, right side + right side, we obtain:
-6x + 9y + 6x + 8y = 39 + 12
or
17y = 51
We divide both sides of equation by 17, to get y.
=> y = 51/17 = 3
Substitute y = 3 back into the first equation of system (or the second equation, it doesn't matter, here we choose the first one).
=> -2x + 3*3 = 13
=> -2x + 9 = 13
=> -2x = 4
=> x = -2
=> The solution of this system is (x, y) = (-2, 3)
Hope this helps!
:)